Determination of Environmental Performance through Environmental Management Accounting: Empirical Evidence from Manufacturing Companies in Indonesia - Urbanus Ura Weruin; Vidyarto Nugroho (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
Environmental sustainability has become a strategic priority for organizations due to increasing ecological challenges, stakeholder expectations, and regulatory pressures. This study aims to examine the effects of market competition, company size, and corporate governance on environmental performance, while also investigating the mediating role of Environmental Management Accounting (EMA). A quantitative explanatory approach was employed using a cross-sectional survey of 126 managers, accounting professionals, environmental managers, and sustainability officers from manufacturing and industrial companies listed on the Indonesia Stock Exchange. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with WarpPLS 8.0. The results indicate that market competition, company size, and corporate governance have significant positive effects on environmental performance. Additionally, all three factors significantly influence the adoption of EMA, with corporate governance demonstrating the strongest effect. EMA was also found to positively affect environmental performance, confirming its strategic role in supporting sustainability-oriented decision-making. Mediation analysis further revealed that EMA significantly mediates the relationships between market competition, company size, corporate governance, and environmental performance. These findings suggest that environmental performance is shaped not only by external competitive pressures and internal organizational characteristics but also by the extent to which environmental information is systematically incorporated into managerial processes. The study contributes to the environmental accounting literature by providing an integrated framework that combines organizational, institutional, and accounting perspectives. Practically, the findings highlight the importance of strengthening EMA practices to support corporate sustainability initiatives, improve environmental outcomes, and enhance long-term organizational competitiveness and legitimacy.